FREEDOM OF SPEECH IN INDONESIAN PRESS: INTERNATIONAL HUMAN RIGHTS PERSPECTIVE - Staples, Clara (Faculty of Law, Universitas Brawijaya, 2016)
This paper will firstly examine the international framework of human rights law and its guidelines for safeguarding the right to freedom of speech in the press. Secondly, it will describe the constitutional and other legal rights protecting freedom of speech in Indonesia and assess their compatibility with the right to freedom of speech under the international human rights law framework. Thirdly it will consider the impact of Indonesia’s constitutional law and criminal and civil law, including sedition and defamation laws, and finally media ownership, on the interpretation and scope of the right to freedom of speech in the press. Consideration of these laws will be integrated with a discussion of judicial processes. This discussion will be used to determine how and in what circumstances the constitutional right to freedom of speech in the press may be facilitated or enabled, or on the other hand, limited, overridden or curtailed in Indonesia. Conclusions will then be drawn regarding the strengths and weaknesses of Indonesian laws in safeguarding the right to freedom of speech in the press and the democratic implications from an international human rights perspective. This inquiry will be restricted to Indonesian laws in existence during the post-New Order period of 1998 to the present, and to the information and analysis provided by English-language sources.